Odpowiedź :
metoda podstawiania:
2x+y=5/-2x
2x-3y=11
y=5-2x
2x-3×(5-2x)=11
y=5-2x
2x-15+6x=11
y=5-2x
8x=26
y=5-2x
x=3,25
y=5-2×3,25
x=3,25
y=-1,5
2x+y=5/-2x
2x-3y=11
y=5-2x
2x-3×(5-2x)=11
y=5-2x
2x-15+6x=11
y=5-2x
8x=26
y=5-2x
x=3,25
y=5-2×3,25
x=3,25
y=-1,5
2x+y=5
2x-3y=11/-1
2x+y=5
-2x+3y= - 11
4y= -6/4
y= - 1,5
2x+y=5
y= -1,5
2x+(-1,5)=5
y=-1,5
2x-1,5=5
y= - 1,5
2x=5+1,5
y= -1,5
2x=6,5/:2
y= -1,5
x=3,25
y= -1,5
2x-3y=11/-1
2x+y=5
-2x+3y= - 11
4y= -6/4
y= - 1,5
2x+y=5
y= -1,5
2x+(-1,5)=5
y=-1,5
2x-1,5=5
y= - 1,5
2x=5+1,5
y= -1,5
2x=6,5/:2
y= -1,5
x=3,25
y= -1,5
2x+y=5
2x-3y=11
y=-2x+5
2x-3(-2x+5)=11
2x+6x-15=11
8x=26/:8
x=3,25
2 razy 3,25+y=5
6,5+y=5
y=5-6,5
y=-1,25
x=3,25
y=-1,25
2x-3y=11
y=-2x+5
2x-3(-2x+5)=11
2x+6x-15=11
8x=26/:8
x=3,25
2 razy 3,25+y=5
6,5+y=5
y=5-6,5
y=-1,25
x=3,25
y=-1,25